Experimental and numerical analysis of the convective flow induced over a dry-ice bank with Particle Image Velocimetry. Issue 1 (1st December 2022) - Vitali, M; Biancini, G; Marchetti, B; Corvaro, F
Abstract: The utilization of carbon dioxide in new technologies opens a wide range of interesting applications which depend strictly upon heat transfer phenomena. The momentum on the deployment of Carbon Capture Utilization and Storage (CCUS) infrastructures will potentially enlarge the diffusion of technologies for the utilization and recycling of CO2 . Such applications, however, require appropriate laboratory investigations for a complete characterization of the CO2 thermo-fluid-dynamic behaviour. The safety management of carbon dioxide is important; thus, accurate modelling is needed since solidification and sublimation of dry-ice can be very challenging to predict analytically. One of the dry-ice applications is the utilisation in refrigeration cycles and in novel CO2 heat pump technologies. For this reason, knowledge about the entity of sublimating CO2 from a solid surface is crucial. This work proposes an innovative experimental setup for the measurement of temperature and convective velocity fields in the sublimating phenomenon of CO2 under atmospheric conditions by means of Particle Image Velocimetry (PIV). The experimental results have been compared and validated with numeric CFD models.